Direct Comparison of Virtual-Histology Intravascular Ultrasound and Optical Coherence Tomography Imaging for Identification of Thin-Cap Fibroatheroma. (October 2015) - Brown, Adam J.; Obaid, Daniel R.; Costopoulos, Charis; Parker, Richard A.; Calvert, Patrick A.; Teng, Zhongzhao; Hoole, Stephen P.; West, Nick E.J.; Goddard, Martin; Bennett, Martin R.
Abstract : Background—: Although rupture of thin-cap fibroatheroma (TCFA) underlies most myocardial infarctions, reliable TCFA identification remains challenging. Virtual-histology intravascular ultrasound (VH-IVUS) and optical coherence tomography (OCT) can assess tissue composition and classify plaques. However, direct comparisons between VH-IVUS and OCT are lacking and it remains unknown whether combining these modalities improves TCFA identification. Methods and Results—: Two hundred fifty-eight regions-of-interest were obtained from autopsied human hearts, with plaque composition and classification assessed by histology and compared with coregistered ex vivo VH-IVUS and OCT. Sixty-seven regions-of-interest were classified as fibroatheroma on histology, with 22 meeting criteria for TCFA. On VH-IVUS, plaque (10.91±4.82 versus 8.42±4.57 mm 2 ; P =0.01) and necrotic core areas (1.59±0.99 versus 1.03±0.85 mm 2 ; P =0.02) were increased in TCFA versus other fibroatheroma. On OCT, although minimal fibrous cap thickness was similar (71.8±44.1 μm versus 72.6±32.4; P =0.30), the number of continuous frames with fibrous cap thickness ⩽85 μm was higher in TCFA (6.5 [1.75–11.0] versus 2.0 [0.0–7.0]; P =0.03). Maximum lipid arc on OCT was an excellent discriminator of fibroatheroma (area under the curve, 0.92; 95% confidence interval, 0.87–0.97) and TCFA (area under the curve, 0.86; 95% confidence interval, 0.81–0.92), with lipid arc ≥80° the optimal cut-off value. Using existing criteria, the sensitivity, specificity, and diagnostic accuracy for TCFA identification was 63.6%, 78.1%, and 76.5% for VH-IVUS and 72.7%, 79.8%, and 79.0% for OCT. Combining VH-defined fibroatheroma and fibrous cap thickness ⩽85 μm over 3 continuous frames improved TCFA identification, with diagnostic accuracy of 89.0%. Conclusions—: Both VH-IVUS and OCT can reliably identify TCFA, although OCT accuracy may be improved using lipid arc ≥80° and fibrous cap thickness ⩽85 μm over 3 continuous frames. Combined VH-IVUS/OCT imaging markedly improved TCFA identification. Abstract : Supplemental Digital Content is available in the text.